An updated description of Galianthe vaginata (Spermacoceae, Rubiaceae), a species endemic to the Serra da Mantiqueira and Serra do Mar, Southeast Brazil - Carmo, João Afonso Martins (2016)
Fil: Carmo, João Afonso Martins . Universidade Estadual de Campinas. Departamento de Biologia Vegetal; Brazil.